(3RGO GdabjQ hLHQ GdcSjQs - (3QGTO Hf gGTe GdQSJGbj GdfYeGfjs
(3ChdgG (B:s
(3Cbhd ebGdG eMcekG heaUdkG dCgd Gdfgj aj GdWH Yde deMJQaj MceI GdWH cGed HMPa CSGfjO heGgh CU`dG s
(3BNQgG (B:s
(3GdMeO ddg Ydi GdEMSGf hGdTcQ dGRGd Ydi GdEjeGf eUdkj Ydi GdfHi hGdBd HY`OI GdCjGe hGddjGd``i s
(3Vef eLehY , JQJjHgG (B: (3ef U (B138 - (3U(B159s
(3CQLhRI TYQjIs
(3GfXQg eY CQLhRI aj GdWH dGHf SjfG Qbe (B"5(3,(B301(3,(B302"s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3fXe s
Keywords: (3GdWHs